Effect of Organic Acid Mixtures on the Extraction Efficiency, Physicochemical, and Thermal Properties of Pigskin Gelatin and Resulting Films - Velazquez, Diego Ezequiel (2025)
Animal tissue by-products, rich in collagen, represent a valuable source of biomaterials. Understanding their physicochemical and thermal behavior is essential for expanding their applications. In this study, pigskin gelatin was extracted through acid hydrolysis using a combination of acetic acid (AH) and either lactic, citric, or ascorbic acid (75:25, v:v, [0.5 M]), followed by thermal denaturation. We evaluated the physicochemical properties of the gelatin solutions (pH, hydroxyproline content, and extraction yield), as well as the macroscopic gel characteristics. Gelatin films were then prepared and analyzed for moisture content, color, and thermal properties. One-way ANOVA was applied to compare treatments, and Pearson’s correlation was used to assess the relationship between the solution pH and physicochemical parameters. Significant differences in the final pH of the solutions were observed among the acid mixture treatments, though the hydroxyproline content and extraction yield were not significantly affected. All gelatin solutions formed stable gels, and the resulting films exhibited similar moisture content. Thermal analysis revealed treatmentdependent variations. Specifically, a significant negative correlation (p < 0.005) was found between the gelatin solution pH and the melting temperature. These results suggest that the use of organic acid mixtures can effectively modulate gelatin properties, offering a versatile approach for tailoring biomaterials for both food and non-food applications.